Case Study : Lieyana Biz Empire - Pizza Muslim By Atar / Fatin Nursuhada Ismail - Ismail, Fatin Nursuhada (2020)
This study has been done to give an idea on how to apply technology solution in real life based on what students learned about technology entrepreneurship. As a statistic student, it is major for everyone to experience a case study for actual business activity. To complete this task, we got the opportunity to interview the owner of the Lieyana Biz Empire which is one of the Pizza Muslim by Atar that located in Pasir Mas, Kelantan. We are gather the general information of this company through telephone interview such as company background, product design, services and the technologies use in that company. Besides, the strategies on how the company promote their products and achievement of this company also collected. While gathering some information from the owner, we can identify a few things about the company’s strengths, weaknesses, opportunities and threats through analysis of SWOT. We were also told some of the problems faced by the company. The problems that we can see in this company are about lack of technology, management and workers. For the further study, we found a great potential to boost the sales if the technology improvement will be made based on the problems. Thus, in this report we will explain in detail about how those technologies can help the company in the future.